Association of lipid metabolism relevant gene FBXW7 polymorphism with coronary artery disease in Uygur Chinese population in Xinjiang, China: a case-control - Abudesimu, Asiya (Int J Clin Exp Pathol, 2017)
Background: Hyperlipidemia is a major risk factor for coronary artery disease (CAD). As F-box and WD repeat domain-containing 7 (FBXW7) gene is an important regulating factor for lipid metabolism, the aim of the present study is to assess the association between human FBXW7 gene polymorphisms and CAD among Han Chinese and Uygur Chinese populations in Xinjiang, China. Methods: A total of 1,312 Han Chinese (650 CAD patients and 662 controls) and 834 Uygur Chinese (414 CAD patients and 420 controls) were enrolled in this case-control study. Three single nucleotide polymorphisms (SNPs) rs2255137 T>C, rs2292743 A>T, rs35311955 G>C of FBXW7 were selected and genotyped using the improved multiplex ligase detection reaction (iMLDR) method. Results: We found that the rs2255137 CC genotype was very common in the CAD patients compared with the control subjects in the Uygur Chinese populations. After adjustments for several confounders: age, gender, smoking, drinking, hypertension, diabetes, TG, TC, HDL-C and LDL-C, this association remained significant. Furthermore, we investigated the relationships between rs2255137 genotypes and the circulating serum lipid levels and found that people carrying the C allele of rs2255137 may have higher serum lipid levels in the Uygur Chinese populations. Conclusion: Our results indicate that rs2255137 in FBXW7 gene is associated with CAD in the Uygur Chinese population in China.